Processing and mechanical properties of novel biodegradable poly-lactic acid/Zn 3D printed scaffolds for application in tissue regeneration. (August 2022) - Pascual-González, C.; de la Vega, J.; Thompson, C.; Fernández-Blázquez, J.P.; Herráez-Molinero, D.; Biurrun, N.; Lizarralde, I.; del Río, J. Sánchez; González, C.; LLorca, J.
Abstract: The feasibility to manufacture scaffolds of poly-lactic acid reinforced with Zn particles by fused filament fabrication is demonstrated for the first time. Filaments of 2.85 mm in diameter of PLA reinforced with different weight fractions of μ m-sized Zn - 1 wt.% Mg alloy particles (in the range 3.5 to 17.5 wt.%) were manufactured by a double extrusion method in which standard extrusion is followed by precision extrusion in a filament-maker machine. Filaments with constant diameter, negligible porosity and a homogeneous reinforcement distribution were obtained for Zn weight fractions of up to 10.5%. It was found that the presence of Zn particles led to limited changes in the physico-chemical properties of the PLA that did not affect the window temperature for 3D printing nor the melt flow index. Thus, porous scaffolds could be manufactured by fused filament fabrication at 190 °C with poly-lactic acid/Zn composites containing 3.5 and 7 wt.% of Zn and at 170 °C when the Zn content was 10.5 wt.% with excellent dimensional accuracy and mechanical properties.